2003
DOI: 10.1615/jlongtermeffmedimplants.v13.i5.40
|View full text |Cite
|
Sign up to set email alerts
|

Experience Improves Successful Use of Fibrin Sealant in Total Knee Arthroplasty: Implications for Surgical Education

Abstract: This study evaluating fibrin sealant application in total knee arthroplasty (TKA) found significant differences in the decline in adjusted hemoglobin loss at 48 hours postoperatively in the treatment group (FS) relative to the control group (C) when the groups were segregated into early and late subgroups. The decline between the late C, 3.53 +/- 0.22 g/dL, and the late FS, 3.01 +/- 0.20 g/dL, was 0.52 g/dL (p = 0.04). The decline between the early C, 3.51 +/- 0.21 g/dL, and the early FS, 3.25 +/- 0.22 g/dL, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…In a later work, in 2003, Wang et al [4] found that a later administration of fibrin sealant seemed to be more efficacious than an earlier application during the procedure.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a later work, in 2003, Wang et al [4] found that a later administration of fibrin sealant seemed to be more efficacious than an earlier application during the procedure.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, the results of five clinical studies of the use of fibrin glues to control bleeding in knee arthroplasty have been reported [4,6,14,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts included work in a variety of surgical disciplines including breast [9, 13, 14, 16, 17, 32, 36], cardiovascular [11, 26, 27, 30, 33], gastrointestinal [10], head and neck [22, 35], hepatic [12, 20], neuro- [29], orthopedic [21, 37, 40, 41], pediatric [12], noncardiac thoracic [25, 30, 31, 33, 34], and vascular surgery [15, 18, 19, 23, 24, 38, 39]. This body of work emphasized the evolving versatility of fibrin sealant because it is capable of causing blood to clot, creating a sealing barrier, and gluing tissues together.…”
Section: Introductionmentioning
confidence: 99%
“…This body of work emphasized the evolving versatility of fibrin sealant because it is capable of causing blood to clot, creating a sealing barrier, and gluing tissues together. Also, these research efforts clarified that fibrin sealant often requires some hands on experience with the agent to maximize its effectiveness [40]. …”
Section: Introductionmentioning
confidence: 99%